The development of novel ionic liquid-based solid catalysts and the conversion of 5-hydroxymethylfurfural from lignocellulosic biomass - Liu, Xiaofang; Luo, Hangyu; Yu, Dayong; Pei, Zhengfei; Zhang, Zhuangzhuang; Li, Can (Frontiers in Chemistry, 2022)
Ionic liquids have attracted much attention because of their excellent properties to be used as a co-solvent, solvent, co-catalyst, catalyst, and so on. This mini-review focus on the novel ionic liquids-based solid catalysts and the applications for 5-Hydroxymethylfurfural production derived from lignocellulosic biomass.